2010
DOI: 10.1007/s00270-010-9950-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Ablation of Osteoid Osteomas with Use of Real-Time Needle Guidance for Accurate Needle Placement: A Pilot Study

Abstract: PurposeTo evaluate the accuracy and technical success of positioning a radiofrequency ablation (RFA) electrode in osteoid osteomas by use of a new real-time needle guidance technology combining cone-beam computed tomography (CT) and fluoroscopy.Materials and MethodsPercutaneous RFA of osteoid osteomas was performed in five patients (median age 18 years), under general anesthesia, with the use of cone-beam CT and fluoroscopic guidance for electrode positioning. The outcome parameters were technical success, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 14 publications
1
30
1
Order By: Relevance
“…Some authors have reported achieved accuracies using CBCT guidance in small patient groups to be ,5 mm in most of their cases [9][10][11]13]; however, these groups are small and there is no or little information on the used needle paths. Nonetheless, this suggests that accuracies of around 3 mm can be reached in clinical practice also, irrespective of the complexity of the needle path and the user experience level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have reported achieved accuracies using CBCT guidance in small patient groups to be ,5 mm in most of their cases [9][10][11]13]; however, these groups are small and there is no or little information on the used needle paths. Nonetheless, this suggests that accuracies of around 3 mm can be reached in clinical practice also, irrespective of the complexity of the needle path and the user experience level.…”
Section: Discussionmentioning
confidence: 99%
“…A deviation of about 7 mm as observed in the case of the double angulated procedures using CT guidance, however, can be expected to impact the treatment outcome. For instance, the targeted small high contrast nidus in radiofrequency ablations of osteoid osteoma is most often ,10 mm [11]. Here, as the ablation zone is approximately 2 cm around the needle tip, a deviation from the target point of .5 mm will result in partial treatment, or even worse, missing the nidus completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OO are mainly found in distal femur and tibia but can occur in almost any bone [3]. Characteristic radiological signs are central, radiotransparent, partly ossifying nidus surrounded by a reactive ossification [4].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, RFA induced the tumor tissue, paravertebral venous plexus or venous plexus within the vertebral body to coagulate to form a 'reactive zone', which can reduce the risk of bone cement leakage, making the bone cement more evenly distributed within the tumor tissues (34). The combination of RFA and PVP technology can largely overcome their own limitations and enhance the complementarity between them (35).…”
Section: Radiofrequency Ablation Combined With Pvp Technologymentioning
confidence: 99%